Principals' leadership in Mexican upper high schools: The paradoxes between rules and practices. (March 2018) - Santizo Rodall, Claudia A; Ortega Salazar, Sylvia B
This article discusses the type of organization and leadership that underlies a competency-based management rule established in Mexico (2008) applicable to principals in public upper high schools. This rule, identified as the 449 Agreement, describes competencies and communicates expected behavior. Implementation, however, is mediated by the principals' interpretation, as found in the semi-structured interviews conducted with a group of selected acting principals. The analysis of this management rule is based on a theory of decision-making and a theory of organizations where different assumptions on peoples' behavior are made. We provide evidence to support the contention that each school principal acts according to its context, and that compliance with the Agreement is not facilitated by its rules design. We conclude that the rules design of the competency-based management model in question is dominated by a perspective of personal heroic leadership that assumes an omniscient and omnipresent manager and that also promotes a centralized management model for all schools. In future research, inquiry could focus on the question of whether transformational leadership based on motivation and instructional leadership based on guidance and coaching for teachers could also be nurtured by rules compatible with the pervasive normative leadership type.